The Design of a Magnetic Separator Machine for Lithium-Ion Battery Enumeration - Yulius Tomy Wijaya; Muhammad Randi Nur Aditya; Muslim Mahardika; Budi Arifvianto; Indra Perdana; Eka Firmansyah; Muhammad Akhsin Muflikhun (Engineering Proceedings, 2025)
The use of lithium-ion batteries for different applications, such as electric vehicles, has increased rapidly in recent decades. Conversely, battery waste is classified as a toxic, hazardous material. In this study, we aimed to design a magnetic separator machine to assist the lithium extraction (mining) process. The design process for this magnetic separator is carried out by calculating the strength of its components, making a 3D design, and analyzing the frame to obtain the Von Mises stress, deformation, maximum shear stress, and safety factor. In our analysis, we found that the largest Von Mises stress in the left frame is 0.872 MPa, the maximum deformation is 6.5 <semantics>× 10−4</semantics> mm, and the maximum shear stress is 0.444 MPa. In the right frame, the Von Mises stress has a maximum value of 0.867 MPa, the maximum shear stress that occurs is 0.443 MPa, and the total deformation is 6.6 × <semantics>10−4</semantics> mm.